Testing the Trade-off theory against the Pecking order theory: An empirical study of Brazilian firms - Banasko, Olaseni (2014)
This study tests the Trade-off theory against the Pecking order on a cross-sectional sample of firms listed on the Brazilian Sao Paolo Exchange. The study covers 1995 – 2013 using 161 Brazilian firm-year observations.